2014
DOI: 10.17221/7685-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Post anaesthetic myelopathy in the horse: a case report

Abstract: ABSTRACT:The first case of post anaesthetic myelopathy in a horse is described. A two year old 530 kg Shire stallion underwent surgical removal of a granuloma in the ventral sternal region under general inhalation anaesthesia in dorsal recumbency. Total duration of the operation was 85 min. The anaesthesia was uneventful except for profuse sweating and arterial hypertension observed during the whole period. During recovery the horse was not able to stand, and flaccid paralysis of hind limbs, absence of reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(37 citation statements)
references
References 12 publications
1
31
0
5
Order By: Relevance
“…Withdrawal reflexes were not reported in this case. As in the case presented here, neurological functions progressively deteriorated over the 12 hours following the end of anaesthesia, finally resulting in incontinence and paralysis of both thoracic limbs 20. observed a progressive muscle paralysis in a case of myelomalacia that eventually led to respiratory impairment before the horse was euthanased, and Zink,19 22 24 reported three cases of myelomalacia that were initially able to rise, only to develop bilateral hindlimb paralysis a few hours later.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Withdrawal reflexes were not reported in this case. As in the case presented here, neurological functions progressively deteriorated over the 12 hours following the end of anaesthesia, finally resulting in incontinence and paralysis of both thoracic limbs 20. observed a progressive muscle paralysis in a case of myelomalacia that eventually led to respiratory impairment before the horse was euthanased, and Zink,19 22 24 reported three cases of myelomalacia that were initially able to rise, only to develop bilateral hindlimb paralysis a few hours later.…”
Section: Discussionsupporting
confidence: 58%
“…In the case presented here, the anaesthesia was uneventful except for a brief period of hypertension and a mild hypoxaemia. Interestingly, of the 31 cases reported to date, six horses also developed arterial hypertension during anaesthesia,13 Brearley and others 1986,20 and in three of the previously unreported cases reported by. 12 Two other authors 15 19 did not measure blood pressure but reported a sudden onset of sweating, a symptom that has been correlated to catecholamine release in humans 21 22 13.…”
Section: Discussionmentioning
confidence: 91%
“…To date only 32 cases of spinal cord myelopathy have been reported. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] It is a poorly understood central neurological condition demonstrated by the variety of names and has been referred to by spinal cord myelomalacia, 17 22 postanaesthetic poliomyelomalacia, 10 postanaesthetic haemorrhagic myelopathy, 23 haematomyelia, 14 spinal cord malacia 9 and postanaesthetic myelopathy. 19 20 Table 1 presents the signalment of previously reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord myelopathy has been reported in 33 cases since 1979 (Schatzmann et al 1979;Blakemore et al 1984;Zink 1985;Brearley et al 1986;Yovich et al 1986;Stolk et al 1991;Lerche et al 1993;Wan et al 1994;Lam et al 1995;Raidal et al 1997;Joubert et al 2005;van Loon et al 2010;Ragle et al 2011;Patschova et al 2014;K€ uls and Rocchi 2017;Hughes et al 2019) and has occasionally been recorded in equine mortality investigations (Johnston et al 2002;Jago et al 2015;. The aetiology of SCM remains unknown; reduced perfusion and ischaemia of the spinal cord in dorsal recumbency (Schatzmann et al 1979), reduced venous return due to compression of the vena cava by abdominal contents (Blakemore et al 1984;Yovich et al 1986;Wan et al 1994), vitamin E deficiency destabilising spinal cord membranes (Stolk et al 1991), stretch ischaemia of the spinal cord, verminous arteritis and embolism (Dugdale and Taylor 2016) have all been suggested.…”
Section: Spinal Cord Myelopathymentioning
confidence: 99%